FROM DOTS TO STOPS-PUBLIC HEALTH INTERVENTION FOR SCHIZOPHRENIA IN LOW AND MIDDLE INCOME COUNTRIES - Farooq, Saeed; Nazar, Zahid; Akhtar, Javaid; Irfan, Muhammad; Naeem, Sher (Journal of Pakistan Psychiatric Society, 2008)
Case management and early intervention strategies are well established for schizophrenia in the industrialized countries, majority of those with schizophrenia in low and middle income countries (LAMICs) do not have access to primary or secondary care psychiatric services. This results in an unacceptably high untreated and partially treated prevalence of the disorder. One of the fundamental problems in achieving and maintaining symptomatic recovery in schizophrenia is the lack of adherence to drug treatment. A number of programmes in LAMICs have shown that providing essential antipsychotic drugs under the supervision of a guardian, usually a relative, results in a significant reduction in the disability, psychotic symptoms and caregiver’s burden. This article proposes a model of public health intervention based on the principles of DOTS (Directly Observed Treatment, Short course) which has been shown to be effective in overcoming non-adherence and maintaining long term treatment for Tuberculosis. We discuss the rationale for translating an intervention from a communicable disease to a non communicable chronic disorder based on preliminary analysis of data from our recent study and discuss how this can be implemented. Keywords: Schizophrenia, Public health, Adherence, Intervention, Effectiveness.